2016
DOI: 10.1073/pnas.1525616113
|View full text |Cite
|
Sign up to set email alerts
|

Structural and biochemical analysis of Bcl-2 interaction with the hepatitis B virus protein HBx

Abstract: HBx is a hepatitis B virus protein that is required for viral infectivity and replication. Anti-apoptotic Bcl-2 family members are thought to be among the important host targets of HBx. However, the structure and function of HBx are poorly understood and the molecular mechanism of HBx-induced carcinogenesis remains unknown. In this study, we report biochemical and structural characterization of HBx. The recombinant HBx protein contains metal ions, in particular iron and zinc. A BH3-like motif in HBx (residues … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
54
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(56 citation statements)
references
References 51 publications
(52 reference statements)
0
54
0
Order By: Relevance
“…3A). HBx contains a BH3-like motif that folds to form an amphipathic α-helix that binds to the conserved BH3-binding groove of Bcl-2, an anti-apoptotic protein (Ma et al, 2008; Jiang et al, 2016). The BH3-like motif may inhibit the anti-apoptotic action of Bcl-2 through interactions with its conserved BH3-binding groove.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…3A). HBx contains a BH3-like motif that folds to form an amphipathic α-helix that binds to the conserved BH3-binding groove of Bcl-2, an anti-apoptotic protein (Ma et al, 2008; Jiang et al, 2016). The BH3-like motif may inhibit the anti-apoptotic action of Bcl-2 through interactions with its conserved BH3-binding groove.…”
Section: Resultsmentioning
confidence: 99%
“…Glu125 and Arg128 of HBx (Fig. 3C) each makes a pair of charge-stabilized hydrogen bonds to residues Arg100 and Asp101 in Bcl-2 (Jiang et al, 2016). The amino acids corresponding to Glu125 and Arg128 in the N-terminus of Cfcec - are Gln9 and Arg12 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The HBx C-terminal has two zinc-finger motif-containing trans-activating regions at aa 58-84 and 120-141 (corresponding to MT3-MT7 and MT20-MT26 in this study), as well as other motifs such as the Bcl-2 homology 3 (BH3)-like motif (aa 110-135) and the H-box motif (aa 88-100; covering MT8-MT12) [9][10][11][12][13][14][15][16] . HBx binds to anti-apoptotic Bcl-2 proteins via the BH3-like motif within HBx (aa 110-135) 17,18 . Mutations within the BH3-like motif at HBx aa 124 and 127 (covering MT21 and MT22) has been reported to prevent its binding to the anti-apoptotic Bcl-2 proteins, thereby abrogating cytosolic calcium elevation, and reducing HBV replication 17,18 .…”
Section: Discussionmentioning
confidence: 99%
“…HBx binds to anti-apoptotic Bcl-2 proteins via the BH3-like motif within HBx (aa 110-135) 17,18 . Mutations within the BH3-like motif at HBx aa 124 and 127 (covering MT21 and MT22) has been reported to prevent its binding to the anti-apoptotic Bcl-2 proteins, thereby abrogating cytosolic calcium elevation, and reducing HBV replication 17,18 . In another study, Guo et al found that the HBx H-box motif regulates HBV replication both positively and negatively through different pathways 14 .…”
Section: Discussionmentioning
confidence: 99%
“…Li et al reported that HBx 111‐117 amino acid residues in c‐terminal played an important role in HBx positioning in the mitochondria, among which aa116 played a decisive role. Replacement of Phe to Cys at aa116 changed HBx binding affinity to Bcl2, which subsequently affected cell apoptosis induced by HBx . Further, cysteine was easy to form disulphide bond, and this amino acid change might disturb HBx protein folding, even impact its transcriptional regulation.…”
Section: Discussionmentioning
confidence: 99%